1999
DOI: 10.1002/(sici)1099-1255(199903/04)14:2<101::aid-jae499>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A non‐linear filtering approach to stochastic volatility models with an application to daily stock returns

Abstract: This paper develops a new method for the analysis of stochastic volatility (SV) models. Since volatility is a latent variable in SV models, it is dicult to evaluate the exact likelihood. In this paper, a non-linear ®lter which yields the exact likelihood of SV models is employed. Solving a series of integrals in this ®lter by piecewise linear approximations with randomly chosen nodes produces the likelihood, which is maximized to obtain estimates of the SV parameters. A smoothing algorithm for volatility estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For some of the series d is however very close to being statistically significant. A similar SVM model was estimated by Fridman and Harris (1998), who studied daily returns on the Standard & Poor's index over the period 1980, and Watanabe (1999, who examined the daily Topix series over the eight year period 1990-1997. Both studies reported significant positive values for the contemporaneous relationship 10 .…”
Section: Estimation Results For the Svm Model And Some Diagnosticsmentioning
confidence: 99%
See 2 more Smart Citations
“…For some of the series d is however very close to being statistically significant. A similar SVM model was estimated by Fridman and Harris (1998), who studied daily returns on the Standard & Poor's index over the period 1980, and Watanabe (1999, who examined the daily Topix series over the eight year period 1990-1997. Both studies reported significant positive values for the contemporaneous relationship 10 .…”
Section: Estimation Results For the Svm Model And Some Diagnosticsmentioning
confidence: 99%
“…7 Jacquier, Polson and Rossi (2001) estimate corr(εt, ηt) and observe a convincing negative relationship between contemporaneous unexpected stock index returns and unexpected volatility. Harvey and Shephard (1996), on the other hand, estimate corr(εt, η t+1 ) and Watanabe (1999) develops an SV model which includes the lagged shock to the return process as an explanatory variable in the variance equation allowing for an asymmetric response. Both studies report negative coefficients for the relation between current unexpected returns and future volatility.…”
Section: Some Theory On the Relationship Between Returns And Volatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We apply the non-linear maximum likelihood method (MLE) proposed byWatanabe (1999) for estimating the SV models throughout this paper. This method is applicable for many types of SV models.…”
mentioning
confidence: 99%
“…This method is applicable for many types of SV models. The number of grids for the numerical integration is set to 50 in this paper as recommended byWatanabe (1999).…”
mentioning
confidence: 99%